The Diversity, Abundance and Distribution of Macroinvertebrates community in the intertidal zone of the Shatt-Al-Arab, South-Iraq. - Khaled Al-Khafaji (University of Thi-Qar Journal of Science, 2019)
The study choosen to evaluate ecological conditions of four stations Al-Dair (1) , Al- Sindibad (2) , Al-Salhiya(3) and Abu Alkasib(4). Monthly samples were taken during the period from December 2011 to December 2012.Some physico- chemical factors were measured for water and sediment, diversity indices of macroinvertebratescommunity , description of their ecology were examined . Water temperature ranged between (11.1- 32.4) ºC. Allstations may categonized as brackish and raged between (1-6.2)psu . Variations in pH values were narrow and withinthe alkaline direction. Oxygen values ranged between (5.07-11.2)mg/L. Detectable monthly changes were found in No3. The former never droped below(6.27)mg at .N No3/L the maximum value was (56.61) mg at .N No3/L.Phosphate values ranged between(1.28-0.03)mg. at. P/L. Localized variations were noticed in percentagecomposition of sediment content of mud, silt and sand. Further, various stations exhibit differences in sedimentcontent of total organio matter . Content of organic matter in sediment of station (2) higher than other station. Thirtynine species of macroinvertebrate belong to (18) families were identified . Gastropoda were the dominant class in allstations , Melanoides tuberculata were dominant species , formed 57, 47, 55 and 53% for the total number of speciesin the station 1, 2, 3 and 4 respectively . Several indices were used to compare among macroinvertebrate species inthe studied stations by richness, diversity , evenness and similarity. The highest values of richness, diversity andeveness were recorded in station (2) which estimated to be 4.04, 2.98 and 0.98 and 0.91 respectively . Keywords:Melanoides tuberculata Macro invertebrates,eveness,diversity,richness.